Genetics of autism spectrum disorders - State, Matthew (Henry Stewart Talks, 2010)
Overview of autism genetics, Rare vs. common variants, Whole genome association, Rare variants and gene discovery, Copy number variation (CNVs), CNVs and autism, Association, Clinical genetics evaluation, Genetic testing